2018
DOI: 10.1038/s41598-018-25770-5
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and Homeostatic Modulation of Multi-Unit Activity in Midbrain Dopaminergic Structures

Abstract: Although the link between sleep disturbances and dopamine (DA)-related neurological and neuropsychiatric disorders is well established, the impact of sleep alterations on neuronal activity of midbrain DA-ergic structures is currently unknown. Here, using wildtype C57Bl mice, we investigated the circadian- and sleep-related modulation of electrical neuronal activity in midbrain ventral-tegmental-area (VTA) and substantia nigra (SN). We found no significant circadian modulation of activity in SN while VTA displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 96 publications
4
20
0
Order By: Relevance
“…Interestingly, an earlier study of glucose utilization in mice reported no day/night difference in either SN region (Jay et al., ). Similarly, MUA in SN of freely moving mice across all vigilance states does not appear to vary across the 24‐hr cycle (Fifel et al., ). However, when MUA during NREM sleep was examined separately, lateral SN showed a day/night difference in LD—with peak activity occurring during the night (Fifel et al., ).…”
Section: Midbrain: Ventral Tegmental Area (Vta) and Substantia Nigra mentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, an earlier study of glucose utilization in mice reported no day/night difference in either SN region (Jay et al., ). Similarly, MUA in SN of freely moving mice across all vigilance states does not appear to vary across the 24‐hr cycle (Fifel et al., ). However, when MUA during NREM sleep was examined separately, lateral SN showed a day/night difference in LD—with peak activity occurring during the night (Fifel et al., ).…”
Section: Midbrain: Ventral Tegmental Area (Vta) and Substantia Nigra mentioning
confidence: 96%
“…Similarly, MUA in SN of freely moving mice across all vigilance states does not appear to vary across the 24‐hr cycle (Fifel et al., ). However, when MUA during NREM sleep was examined separately, lateral SN showed a day/night difference in LD—with peak activity occurring during the night (Fifel et al., ). Given that DA release in the dorsal striatum exhibits a clear 24‐hr rhythm (Hood et al., ) and receives input from DA neurons of the SN, future work should examine if daily rhythms are present in the different nigral cell types (i.e., DA and GABA).…”
Section: Midbrain: Ventral Tegmental Area (Vta) and Substantia Nigra mentioning
confidence: 96%
See 1 more Smart Citation
“…DNspecific borders also contained cell specialization related genes, such as genes related to circadian regulation. Midbrain DNs have an important role in the homeostatic circadian and sleep-related modulation of neuronal activity 48 .…”
Section: Fig S4f)mentioning
confidence: 99%
“…Neuronal activity in the VTA exhibits arousal-state-dependent alterations, with increased activity during wakefulness and REM sleep compared to NREM sleep (Miller et al, 1983;Fifel et al, 2018). Although initial studies suggested that VTA-dopaminergic neurons do not change their mean firing rate across sleep/wake states (Miller et al, 1983;Steinfels et al, 1983), more recent examinations revealed marked arousal statedependent alterations in both firing rate and firing pattern (Dahan et al, 2007;Gomperts et al, 2015).…”
Section: Introductionmentioning
confidence: 99%